1992
DOI: 10.1002/mrd.1080320312
|View full text |Cite
|
Sign up to set email alerts
|

Morphological development and sex of bovine in vitro‐fertilized embryos

Abstract: Bovine in vitro-fertilized embryos at the blastocyst stage were collected at days 7, 8, and 10 postinsemination and sex was determined via the polymerase chain reaction (PCR) to compare the embryonic development with the sex of the embryos. The percentages of males (sex ratio) after division of the embryos into three developmental groups were 68%, 48%, and 35% in the fast, intermediate, and slow groups, respectively (P = 0.014). The percentages of males on days 7, 8, and 10 were 60%, 40% and 33%, respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(62 citation statements)
references
References 18 publications
4
56
0
2
Order By: Relevance
“…However, the selection of embryos for sexing was performed differently in these studies. Our results might therefore be in accordance with other studies, indicating that glucose in the medium possibly favours a more rapid cleavage and growth of male embryos over females (Bredbacka & Bredbacka 1996, Peippo et al 2001, the latter having a slower cleaving process (Avery et al 1991(Avery et al , 1992 and being less capable of progressing from the morula/early blastocyst stage to more advanced stages of development (Larson et al 2001). Nevertheless, the study of sex ratio differences was beyond the scope of this experiment.…”
Section: Discussionsupporting
confidence: 93%
“…However, the selection of embryos for sexing was performed differently in these studies. Our results might therefore be in accordance with other studies, indicating that glucose in the medium possibly favours a more rapid cleavage and growth of male embryos over females (Bredbacka & Bredbacka 1996, Peippo et al 2001, the latter having a slower cleaving process (Avery et al 1991(Avery et al , 1992 and being less capable of progressing from the morula/early blastocyst stage to more advanced stages of development (Larson et al 2001). Nevertheless, the study of sex ratio differences was beyond the scope of this experiment.…”
Section: Discussionsupporting
confidence: 93%
“…Embryos produced in vitro in a number of species fall into fast-cleaving and slow-cleaving groups, which are predominantly male and female, respectively. This phenomenon has been observed for bovine (1)(2)(3)(4)(5),** mouse (6,7), sheep (8,9), and human embryos (10). In vivo-produced male pig embryos, both before and subsequent to hatching from the zona pellucida, have also been reported to be larger and to have more cells than female embryos (11,12).…”
mentioning
confidence: 68%
“…Recent studies support this notion (Avery et al, 1992;Xu et al, 1992;Pergament et al, 1994;Kochhar et al, 2003;). Male embryos created by in vitro fertilization grow faster before implantation than female embryos, and these fi ndings support a genetic cellular difference between the sexes that exists before the induction of hormonal stimulation (Avery et al, 1992;Xu et al, 1992;Pergament et al, 1994;Kochhar et al, 2003). Sex-related differences in the expression of genes during early embryo development have also been observed: females exhibit higher mRNA levels of glucose-6-phosphate dehydrogenase and hypoxanthine A role for cell sex in stem cell-mediated skeletal muscle regeneration: female cells have higher muscle regeneration effi ciency W e have shown that muscle-derived stem cells (MDSCs) transplanted into dystrophic (mdx) mice effi ciently regenerate skeletal muscle.…”
mentioning
confidence: 83%